Mucosal Atrophy Predicts Poorer Outcomes in Pediatric Ulcerative Colitis—A National Inception Cohort Study. Issue 5 (22nd February 2023) - Stenke, Emily; Stallard, Lorraine; Cooper, Sarah; Dominik, Anna; Pilkington, Abigail; Sugrue, Sheila; O'Sullivan, Maureen; McDermott, Michael; Quinn, Shoana; Broderick, Annemarie; Bourke, Billy; Hussey, Séamus
Abstract : Background: Outcomes in pediatric ulcerative colitis (UC) are heterogeneous and predictors of disease course eagerly sought. Mucosal atrophy (MA) is characterized by histological abnormalities of colonic intestinal glands. Objective: To determine the prevalence of MA in a national inception cohort of pediatric UC and its impact on outcomes. Methods: Irish children < 16 years old with UC are diagnosed at a single referral center. At diagnosis, patients underwent phenotyping by Paris classification and activity assessment by Pediatric Ulcerative Colitis Activity Index. Biopsies from all colonic segments were evaluated for MA. Patients were followed prospectively. The primary outcome was corticosteroid-free remission at 1 year. Secondary outcomes included relapse, treatment escalation, and colectomy by 2 years. Results: Of 251 pediatric patients with UC (mean age 11.8 years, 55% male), 38 (15%) had MA on diagnostic biopsy. Baseline characteristics were similar between groups with/without MA and there was no difference in steroid-free remission or rates of moderate-severe UC at 1 year. Patients with MA had higher use of steroids (29% vs 15%, P = 0.04) and immunomodulators (40% vs 21%, P = 0.04) at 6 months, higher biologic use at 1 year (34% vs 16%, P = 0.03), earlier first relapse (mean ± SD 29.4 ± 26.1 vs 46.7 ± 43.4 weeks after diagnosis, P = 0.02), and higher colectomy rates by 2 years (21% vs 8%, P = 0.01). Conclusions: Children with MA at diagnosis had higher colectomy rates despite earlier treatment escalation and similar baseline severity scores. We identify MA as a promising new prognostic marker in children with newly diagnosed UC. Abstract :